Evaluación del potencial de un residuo proveniente de la industria panelera como fuente de carbono para la producción de biomasa microalgal (2017)
In this project the influence of a residue of the 'panela' industry as a crop supplement on the production of biomass and lipids in the microalga Chlorella vulgaris was evaluated. Foliar fertilizer (FOLIAGRO) was used as a culture medium and two of the residues of the panela, melote and wash water were evaluated in different volume / volume (V / V) ratios as a supplement. The microalgae were cultured in photobioreactors adapted to room temperature, photoperiods of 12 hours light / 12 hours darkness with incandescent light lamp and constant stirring by means of aquarium pumps. Cultures were monitored for 10 days for the pre-experiments and 15 days for the experiment, using the Neubauer chamber and a binocular microscope. Cell concentration was evaluated by means of growth curves. To obtain biomass the culture was allowed to settle by stirring, each sample was centrifuged and the wet biomass obtained (up to 90% moisture) was dried at 40 ° C for 17 hours. Subsequently, the lipids were extracted by solvents and by means of A gas chromatography was determined the lipid profile.